2000
DOI: 10.1016/s1074-7613(00)00052-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antigen-Specific Antitumor Immunity with Altered Peptide Ligands that Stabilize the MHC-Peptide-TCR Complex

Abstract: T cell responsiveness to an epitope is affected both by its affinity for the presenting MHC molecule and the affinity of the MHC-peptide complex for TCR. One limitation of cancer immunotherapy is that natural tumor antigens elicit relatively weak T cell responses, in part because high-affinity T cells are rendered tolerant to these antigens. We report here that amino acid substitutions in a natural MHC class I-restricted tumor antigen that increase the stability of the MHC-peptide-TCR complex are significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
290
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(303 citation statements)
references
References 57 publications
13
290
0
Order By: Relevance
“…We presumed that the improved immunogenicity of W5F might be partly due to better engagement by the TCR, since the PMFScore value predicted increased interaction between the TCR and W5F-HLA-A2 complex. As reported by Slansky and colleagues, the enhanced immunogenicity of an APL of a gp70 tumor epitope correlated with an enhanced binding affinity between the TCR with the pMHC complex compared with the WT epitope [9]. In addition, the result from the HLA presentation study showed that the conservative substitutions did not cause any alteration in MHC binding.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…We presumed that the improved immunogenicity of W5F might be partly due to better engagement by the TCR, since the PMFScore value predicted increased interaction between the TCR and W5F-HLA-A2 complex. As reported by Slansky and colleagues, the enhanced immunogenicity of an APL of a gp70 tumor epitope correlated with an enhanced binding affinity between the TCR with the pMHC complex compared with the WT epitope [9]. In addition, the result from the HLA presentation study showed that the conservative substitutions did not cause any alteration in MHC binding.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, several APL with TCR contact residues mutation were originally identified using single specific T-cell clone in vitro, and these APL were much more efficient at expanding and activating the WT specific T-cells pool besides the original T-cell clone [9,14]. These studies and www.eji-journal.eu our findings strongly suggest that a large T-cell repertoire exists in vivo, whose TCR displays common structural features and reactivity patterns to original T-cell clone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that CTLs induced by in vitro sensitization using the modified peptide exhibited better recognition of the native peptide compared with CTLs raised with the native peptide (82). Substitutions of amino acids of a peptide epitope, for example, can greatly increase the binding affinity without interfering with the peptide recognition (83)(84)(85)(86). Most of the immunogenic melanoma and melanocyte differentiation antigen peptides have a moderate or relatively low affinity for the HLAA*0201 molecule, in contrast to viral peptides that have high binding affinity for their corresponding MHC-I (87-90).…”
Section: Modification Of Peptidesmentioning
confidence: 99%